When Lincoln Came to Egypt - Smith, George Washington, 1855-1945 (Book collections on Project MUSE., 2016)
"In When Lincoln Came to Egypt, George W. Smith discusses Lincoln's various trips to southern Illinois, focusing mainly on Lincoln's most prominent visit, when he came to debate Stephen A. Douglas in Jonesboro in 1858"--